Identifikasi dan Pemetaan Pohon Sarang Orangutan Sumatera (Pongo abelii) di Kawasan Penyangga Cagar Alam Dolok Sibual-buali (Studi Kasus : Desa Bulu Mario, Aek Nabara dan Huraba) - Etti Nur Cahyani; Anita Zaitunah; Pindi Patana (Peronema Forestry Science Journal, 2016)
The research was conducted in March – August 2014 in Bulu Mario, Aek Nabara and Huraba Villages. Research method used line transect and purposive sampling. This research aims to identification and mapping of the tree and nest of Sumatran Orangutan (Pongo abelii) in Dolok Sibual-buali Nature Reserve buffer zone (Bulu Mario, Aek Nabara and Huraba villages). The results showed that the most trees were used as the nest of Sumatran Orangutan (Pongo abelii) were  Syzygium sp. (Hau Dolok) and Quercus gemelliflora Blume (Hoteng) trees. The trees have the meeting branch, a series of many leaves and twigs, the trees weren’t Sumatran Orangutan’s feed with hight 11-15 m, diameter 20-30 m, branch pattern was adjacent, type of canopy was irregular shape and spherical, and nest high 11-15 m. The position of the nest is most commonly found nesting in position I (near by the main branch) and nest type is C (the nests are made of Orangutan still looks intact, but most of the leaves have started to wilt and there are small holes in the nests). The distribution of the nest and trees of Sumatran Orangutan (Pongo abelii) had clumped spasial patterns of distribution, with a dispersion index of 1.25, was on flat-very steep slope, altitude 401-1400 meters above sea level and had NDVI values 0.15-0.61, mixed plantation and secondary forests in the villages around of Dolok Sibual-buali Natural Reserve, exactly in Bulu Mario, Aek Nabara and Huraba villages.Keywords : Pongo abelii, Syzygium sp., Quercus gemelliflora Blume, Identification and Mapping of the Tree and Nest of Sumatran Orangutan